Activity Based Costing, Efisiensi Biaya dan Kinerja Keuangan - Jihan Rahmah Fadiyah; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2025)
The ABC Method emerged in response to the weaknesses of traditional methods, such as the production volume-based cost calculation method. The purpose of this study is to analyze the Application of the Activity-Based Costing (ABC) Method in Measuring Cost Efficiency and Financial Performance. The research method used is literature study or Library Research with a qualitative approach. The literature used is literature from the results of research or reviews presented in national and international scientific articles that are in accordance with accounting. All articles used are sourced from Mendeley's literacy data search engine and Google scholar. Based on a literature review from several articles on the results and discussion, the conclusions that can be drawn are: The application of the Activity-Based Costing (ABC) Method has a significant impact on cost efficiency and the company's financial performance.